2013
DOI: 10.1111/jcmm.12066
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide induces a fibrotic‐like phenotype in endothelial cells

Abstract: Endothelial dysfunction is crucial in endotoxaemia-derived sepsis syndrome pathogenesis. It is well accepted that lipopolysaccharide (LPS) induces endothelial dysfunction through immune system activation. However, LPS can also directly generate actions in endothelial cells (ECs) in the absence of participation by immune cells. Although interactions between LPS and ECs evoke endothelial death, a significant portion of ECs are resistant to LPS challenge. However, the mechanism that confers endothelial resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
63
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 65 publications
15
63
0
Order By: Relevance
“…We previously reported that bacterial endotoxins induce the conversion of ECs into activated fibroblasts, also known as myofibroblasts (9). Endotoxin-induced endothelial fibrosis is mediated through a process known as endothelial-to-mesenchymal transition (EndMT), which has been studied using transforming growth factors ␤1 and ␤2 (TGF-␤1 and TGF-␤2) as EndMT inducers (10,11).…”
mentioning
confidence: 99%
“…We previously reported that bacterial endotoxins induce the conversion of ECs into activated fibroblasts, also known as myofibroblasts (9). Endotoxin-induced endothelial fibrosis is mediated through a process known as endothelial-to-mesenchymal transition (EndMT), which has been studied using transforming growth factors ␤1 and ␤2 (TGF-␤1 and TGF-␤2) as EndMT inducers (10,11).…”
mentioning
confidence: 99%
“…41,56,57 Furthermore, we recently demonstrated that the endotoxin lipopolysaccharide induces the acquisition of fibrotic-like phenotype in ECs. 37 This conversion rises as a potential mechanism that begins endothelial dysfunction during the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…ECs in the absence of H 2 O 2 showed VE-cadherin labeling that was localized predominantly to the plasma membrane (Figure 2a To demonstrate that our findings were obtained from a culture of human ECs without contamination from fibroblast-like cells, we carried out an exhaustive inspection of the EC culture. 37 To that end, we used the specific endothelial marker VE-cadherin and the specific fibrotic protein, FSP-1. We found that 499% of cells in the EC culture were positive for VE-cadherin, whereas those expressing FSP-1 were not detected.…”
Section: H 2 O 2 Induces the Conversion Of Ecs Into Myofibroblastsmentioning
confidence: 99%
See 2 more Smart Citations